Thermodynamic studies on removal of reactive blue 19 dye on cross-linked chitosan/oil palm ash composite beads - Masitah, Hassan; Bassim H., Hameed, Prof. Dr.; Abdul Latif, Ahmad, Prof. (Universiti Tenaga Nasional, 2011)
The International Conference on Energy and Environment 2009 (ICEE 2009) organized by Universiti Tenaga Nasional from 7th - 8th December 2009 at Equatorial Hotel, Malacca, Malaysia.